6-Sulfo LacNAc (Slan) as a Marker for Non-classical Monocytes - Hofer, Thomas P.; van de Loosdrecht, Arjan A.; Stahl-Hennig, Christiane; Cassatella, Marco A.; Ziegler-Heitbrock, Loems (Frontiers in Immunology, 2019)
Monocytes are subdivided into three subsets, which have different phenotypic and functional characteristics and different roles in inflammation and malignancy. When in man CD14 and CD16 monoclonal antibodies are used to define these subsets, then the distinction of non-classical CD14low and intermediate CD14high monocytes requires setting a gate in what is a gradually changing level of CD14 expression. In the search for an additional marker to better dissect the two subsets we have explored the marker 6-sulfo LacNAc (slan). Slan is a carbohydrate residue originally described to be expressed on the cell surface of a type of dendritic cell in human blood. We elaborate herein that the features of slan+ cells are congruent with the features of CD16+ non-classical monocytes and that slan is a candidate marker for definition of non-classical monocytes. The use of this marker may help in studying the role of non-classical monocytes in health and in diagnosis and monitoring of disease.